Professional Staff as Leaders in Enhancing Student Engagement : Building Capacity in Emerging Technologies Through Cascade and Viral Leadership (The ALTC-Viral Leadership Project) : Final Report. - Cluett, Lisa (Office for Learning and Teaching, 2012)
Final report from a project whose goals were threefold: (1) to develop an ongoing, Western Australian-based network of professional staff leaders who foster student engagement through emerging technologies, (2) to design, implement and evaluate web-based resources to support this network and to ensure its continuity, and (3) to create a new model of leadership for application in the tertiary sector, based on applying the cascade/viral model to building leadership capacity. The first phase of the project consisted of a structured learning component, and the establishment of a community of leaders across three Western Australian institutions. Subsequent phases developed this community through mentoring, networking and community activities, all under the auspices of a new cascade and viral leadership model. The growing community of leaders in Western Australia who are able to recognise, initiate and integrate emerging technologies into the engagement of students will be a lasting legacy of the project.